Attitude of students in the high schools of Quezon City and University of the Philippines towards the teaching of Spanish - Abad, Jesusa (Henson) 1911- (s.n.], 1959)
The objectives of the study are: (1) to know the general attitudes towards the teaching of Spanish to students in the high schools of the University of the Philippines and Quezon City, (2) to determine the factors that have influenced these general attitudes; and (3) to gather information about the subject matter, the teacher, and methods of teaching.